Comparision between the Glasgow Coma Scale and Glasgow Coma Scale Pupil reactivity score in predicting mortality in traumatic brain injury patients - Koirala, Puspa; Shrestha, Dipendra; Phuyal, Suman; Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2022)
Introduction: Glasgow Coma Scale (GCS) and the pupillary response are the key indicators of the severity of traumatic brain injury (TBI). Glasgow coma scale- Pupil reactivity (GCS-P) score is a tool to incorporate pupil reactivity and GCS into a simple single index. The main aim of this study was to compare GCS and GCS- P scores in predicting mortality in TBI patients in our institution. Materials and Methods: All patients admitted to Tribhuvan University Teaching Hospital (TUTH) with moderate to severe head injury from May 2018 to April 2019 were included in the study. Both GCS and GCS- P scores were recorded separately at admission. Outcome was measured with Glasgow Outcome Scale (GOS) at the time of discharge and in three months. Diagnostic accuracy of both these scoring systems were calculated using receiver-operating characteristics (ROC) curve, and correlation between them was estimated by using Pearson correlation coefficient. Results: Out of 136 patients enrolled, 98 patients had favorable outcome, 38 patients had unfavorable outcome at discharge. The Pearson correlation coefficient between GCS and GOS at discharge was 0.721 and GCS-P and GOS was 0.740 showing a good correlation between the GCS and GOS and GCS-P and GOS. The areas under ROC curve for GCS for prediction of mortality was 0.856 (95% CI; p<0.001) and for GCS-P is 0.871(95%CI;p<0.001) suggesting good discriminatory ability of both models. However, on statistical analysis, the discriminatory ability of GCS-P was not superior to GCS for mortality. Conclusion: GCS-P is as good as but not superior to GCS in predicting mortality in traumatic brain injury patients.